The Nazi persecution of the gypsies - Lewy, Guenter, 1923- (Oxford University Press, 2000)
Roaming the countryside in caravans, earning their living as musicians, peddlars, and fortune-tellers, the gypsies and their elusive way of life represented an affront to Nazi ideals of social order, hard work and racial purity. They were branded as "asocials," harassed, and eventually herded into concentration camps where many thousands were killed.; In this work, the author draws upon thousands of documents from German and Austrian archives to provide a comprehensive study of the fate of the gypsies under the Nazi regime. The author traces the escalating vilification of the gypsies as the Nazis instigated a widespread crackdown on the "work-shy" and "itinerants." But he also shows that Nazi policy towards gypsies was confused and changeable.